2016
DOI: 10.1103/physrevb.93.144417
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced perpendicular magnetic anisotropy inLa2CoMnO6ɛthin films and its dependence on film thickness

Abstract: Ferromagnetic insulating La 2 CoMnO 6- (LCMO) epitaxial thin films grown on top of SrTiO 3 (001) substrates present a strong magnetic anisotropy favoring the out of plane orientation of the magnetization with a large anisotropy field (70 kOe for film thickness of about 15 nm). Diminishing oxygen off-stoichiometry of the film enhances the anisotropy. We attribute this to the concomitant shrinkage of the out of plane cell parameter and to the increasing of the tensile strain of the films. Consistently, LCMO fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
4
21
1
Order By: Relevance
“…S1). As reported in our previous work, films grown on SrTiO 3 substrates are under tensile strain and exhibit strong PMA 21 . Magnetic properties of the barrier are not clearly determined via SQUID magnetometry because magnetic signal of such a thin film is very low.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…S1). As reported in our previous work, films grown on SrTiO 3 substrates are under tensile strain and exhibit strong PMA 21 . Magnetic properties of the barrier are not clearly determined via SQUID magnetometry because magnetic signal of such a thin film is very low.…”
Section: Resultssupporting
confidence: 75%
“…u ., which suggest a high degree of Co/Mn cationic ordering 19,20 . We have also shown that LCMO grown under tensile strain (on STO) exhibits a strong perpendicular magnetic anisotropy (PMA), which has a magnetocrystalline origin due to the spin-orbit coupling (SOC) in Co 2+ ions 20,21 . This suggests that LCMO is a good candidate to exhibit tunneling anisotropic magnetoresistance (TAMR).…”
Section: Introductionmentioning
confidence: 95%
“…When the magnetic field is applied perpendicular to the sample plane (the OP configuration), saturation is reached at~30 kOe, while when the field is applied parallel to the sample plane (the IP configuration), saturation is not reached even at 80 kOe. Thus, the perpendicular-to-plane direction is the easy magnetization direction, as previously observed in samples grown by RF magnetron sputtering 23,35 . Our previous results for samples prepared by RF sputtering indicate that the Co 2+ valence state is preferentially stabilized irrespective of the structural strain even in nonstoichiometric samples 36 .…”
Section: Resultssupporting
confidence: 70%
“…b High-resolution XRD pattern of the (002) diffraction peak. The oscillations around the main diffraction peak are an indication of the high structural quality of the epitaxial LCMO films contribution to the magnetic moment of Co 2+ occurs and generates a strong perpendicular magnetic anisotropy 35,36 , as in the present case. On the other hand, M(H) loops in Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation